Intraoperative Invasive Blood Pressure Monitoring in Flap-Based Breast Reconstruction: Does It Change Outcomes?. Issue 1 (January 2021) - Dekker, Paige K.; Noe, Niki; Bekeny, Jenna C.; Lavin, Christopher; Zolper, Elizabeth G.; Song, David H.; Fan, Kenneth L.
Abstract : Background: Despite the lack of guidelines regarding the use of intra-arterial lines in postmastectomy breast reconstruction (PMBR), they continue to be used in this setting. In this study of patients undergoing PMBR, we aimed to (1) identify factors associated with intra-arterial line placement, (2) analyze the correlation between intra-arterial monitoring and noninvasive blood pressure (NIBP) monitoring, and (3) investigate whether hemodynamic management differs significantly between patients undergoing intra-arterial blood pressure monitoring versus NIBP. Methods: All patients undergoing flap-based PMBR between 2017 and 2019 were retrospectively reviewed. Patients were pair-matched based on flap donor site, BMI, and age to identify factors associated with intra-arterial line placement. Methods described by Bland and Altman1 were utilized to determine agreement between intra-arterial line measurements and NIBP. Results: Thirty-two patients were included with 16 patients in the intra-arterial line group and 16 in the NIBP group. None of the factors studied were significantly related to the likelihood of intra-arterial line placement. Agreement analysis demonstrated that mean arterial pressures calculated from intra-arterial line readings were as much as 23 points lower or 12 points higher than those from NIBP. Bias calculations with this extent of difference suggest poor correlation between intra-arterial line readings and NIBP. There was no difference between groups in rate of administration of blood-pressure altering medications (hypertensive: n = 3, 18.8%, P = 1.000; hypotensive: n = 7, 3.8%, P = 1.000). Conclusion: Our findings highlight the need for more definitive guidance regarding the use of intra-arterial monitoring in patients undergoing PMBR.